Adult dental anxiety in the Finnbrain Birth Cohort Study - changes and relations to psychological well-being - Hagqvist, Outi (fi=Turun yliopisto|en=University of Turku|, 2021)
This thesis presents results from a longitudinal study of dental anxiety that aimed to evaluate changes in dental anxiety during and after pregnancy in the FinnBrain Birth Cohort. The study also evaluated associations between dental anxiety, general anxiety, depression, trauma outside dental settings and parental bonding. Data were provided by 201 women and 147 men taking part in the pilot phase of the study, and by 3808 women and 2623 men in the main phase of the study. Participants completed the Modified Dental Anxiety Scale as a valid measure of dental anxiety during the first and third trimesters of pregnancy and 3 months after the childbirth. The MDAS was also completed in the pilot study12 and 24 months after the baby was born. Depression, general anxiety, pregnancy-related anxiety, mental, physical and sexual trauma, positive and negative life events and parental bonding were all measured by valid questionnaires. Most participants were non-anxious in both cohorts, but approximately every fifth participant experienced changes in their dental anxiety. The prevalence of high dental anxiety at baseline was 8% in the pilot and 8% in the actual cohort among women and 3% in the pilot and 5% in the actual cohort among men. Overall, women were more fearful than men. Dental anxiety, depression and general anxiety correlated in the main cohort, but the magnitudes of the correlations were modest. In the pilot population, the correlations were statistically significant only among men. In the pilot cohort dental anxiety correlated positively with emotional trauma among men and with the number of life events among women but not with parental bonding. The findings suggest that dental anxiety is not a stable phenomenon for everyone. It could be influenced by specific life events such as stressors or hormonal changes during pregnancy. Dental clinicians should measure dental anxiety regularly and consider different etiological aspects in the individualized anxiety treatments.

Aikuisten hammashoitopelko FinnBrain-kohortissa –pelon muutokset ja yhteydet psyykkiseen hyvinvointiin Tämä väitöskirja raportoi tuloksia hammashoitopelon seurantatutkimuksesta FinnBrain-kohortissa. Tutkimuksen tavoitteena oli arvioida hammashoitopelon muutoksia raskauden aikana ja sen jälkeen sekä arvioida pelon yhteyttä ahdistuneisuuteen, masennukseen ja erilaisiin elämänkokemuksiin. Tutkimusaineisto koostui 201 naisesta ja 147 miehestä tutkimuksen pilottikohortista sekä 3808 naisesta ja 2623 miehestä pääkohortista. Osallistujat täyttivät hammashoitopelkokyselyn (Modified Dental Anxiety Scale) raskauden ensimmäisen ja viimeisen kolmanneksen aikana sekä 3 kk synnytyksen jälkeen, pilottiaineistossa myös 12 ja 24 kk kuluttua synnytyksestä. Ahdistuneisuutta, erikseen myös raskauteen liittyvää ahdistuneisuutta, masentuneisuutta, psyykkisiä, fyysisiä ja seksuaalisia traumoja, positiivisia ja negatiivisia elämäntapahtumia sekä kokemuksia omista vanhemmista arvioitiin kyselylomakkein. Suurin osa osallistujista ei pelännyt hammashoitoa, mutta noin joka viidennellä oli muutoksia hammashoitopelossa tutkimusjakson aikana. Paljon hammashoitopelkoa esiintyi tutkimuksen alussa 8 %:lla naisista sekä pilotti- että pääkohortissa, miehistä 3 %:lla pilotissa ja 5 %:lla varsinaisessa kohortissa. Naiset raportoivat ylipäätään enemmän pelkoa kuin miehet. Hammashoitopelko, masentuneisuus ja ahdistuneisuus olivat yhteydessä toisiinsa pääkohortissa, mutta yhteys oli lievä. Pilottikohortissa lievä yhteys löytyi ainoastaan miehillä. Pilottikohortissa miehillä löytyi heikko yhteys hammashoitopelon ja henkisten traumojen välillä, naisilla pelon ja elämäntapahtumien määrän välillä. Hammashoitopelko ei yhdistynyt koehenkilöiden muistoihin omien vanhempiensa vanhemmuudesta. Tulokset viittaavat siihen, että hammashoitopelko ei ole pysyvä ilmiö. Siihen saattavat vaikuttaa erilaiset elämäntapahtumat ja stressitekijät tai jopa raskauden aikaiset hormonaaliset muutokset. Suunterveyden ammattilaisten tulisi mitata hammashoitopelkoa säännöllisesti, ja pelon hoito tulisi suunnitella yksilöllisesti mahdollisten etiologisten tekijöiden mukaan.